2021
DOI: 10.1007/s00502-021-00943-9
|View full text |Cite
|
Sign up to set email alerts
|

The current state of research on energy communities

Abstract: The introduction of the Clean energy for all Europeans package by the European Union (EU) led to a significant boost of public and research interest in energy communities. However, since neither their definition nor their goals are clearly defined, there is a very broad field of research on this topic. This paper aims to classify existing research on energy communities and to analyze what this umbrella term looks like in the literature. First, a literature review is conducted with regard to energy communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 68 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…The concept of an EC is open to different definitions [1,8] and interpretations [2,11]. In this article, we are, firstly, interested in understanding the modalities in which people decide to be part of ECs [25] by examining the possible "drivers", conceptualized as follows:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of an EC is open to different definitions [1,8] and interpretations [2,11]. In this article, we are, firstly, interested in understanding the modalities in which people decide to be part of ECs [25] by examining the possible "drivers", conceptualized as follows:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition to the technical benefits related to ECs (e.g., optimizing and building more sustainable and efficient energy vectors), social aims have been added to the discussion, emphasizing the benefits of improving social cohesion among participants, or aspiring members, of the community [8,9]. These aspects have been integrated and promoted at the European legislative level through (i) the "Clean Energy for All Europeans" package, which introduced and defined the concept of "energy communities" [10,11]; (ii) the directive on common rules for the internal electricity market Energies 2023, 16, 5872 2 of 13 (EU 2019/944), which aimed at improving the diffusion of ECs and facilitating the efficient integration of citizens (as active participants) in the electricity production system [12,13]; and (iii) the revised Renewable Energy Directive (2018/2001/EU, RED II), which strengthened the role of renewable energy consumers and ECs. In Italy, the legislative framework is defined by the Decreto Milleproroghe ("Thousand extensions" Decree-Law, 2020), which introduced the definitions of "renewable energy communities" and "energy consumers acting autonomously and collectively".…”
Section: Introductionmentioning
confidence: 99%
“…For example, wind energy can be produced in energy communities in two ways: with micro wind turbines at the household level or with large-scale wind turbines at the EC level. There are a few examples in the literature of ECs powered solely by wind microturbines [28], mainly in Northern Europe (Belgium, Denmark, France, Germany, and Sweden), as a wind turbine with both a vertical and horizontal axis requires a minimum wind speed (cut-in) of around 4 m/s in a constant direction. Studies have shown very low performance for a micro-wind turbine in an Italian urban area for most of the year, and the technology has been deemed unsuitable or economically disadvantageous [29].…”
Section: Energy Community and Energy Poverty: A Virtuous Model Betwee...mentioning
confidence: 99%
“…Gruber et al [31] also reached a conclusion that wind capacity should be taken into consideration appropriately for the performance of the micro-wind turbines.…”
Section: Literature Reviewmentioning
confidence: 99%